The influence of various toxic effects on the cornea and changes in corneal light transmission - Cejka, Cestmír; Ardan, Taras; Sirc, Jakub; Michálek, Jiří; Brůnová, Blanka; Cejková, Jitka (Graefe's archive for clinical and experimental ophthalmology, 2010)
PURPOSE: Normal corneal hydration is necessary for the maintenance of corneal transparency. Damage of the corneal epithelium or endothelium by various external influences disturbs the mechanism by which the cornea maintains normal hydration and transparency. The cornea swells, and the corneal thickness increases, resulting in increased scatter and the development of corneal opacity. The transmission of light across the cornea is changed. The purpose of this study is to investigate spectrophotometrically the corneal light transmission under the influence of the various factors affecting the cornea. METHODS: We developed a spectrophotometric method to measure the light transmission across the cornea under the influence of various factors affecting the cornea, such as treatment with 0.9% NaCl, saline, or phosphate buffered saline (PBS), solutions employed as placebo eye drops (negative controls) in experimental studies, agents toxic to the cornea, such as diluted acids or alkalis. The method distinguishes between changes in corneal light transmission caused by altered corneal thickness (the level of hydration) and changes resulting from other corneal disturbances which in turn affect corneal light transmission. RESULTS: The results obtained show that the corneal light transmission is decreased following the application of toxic substances on the corneal surface. This decrease is highly dependent on the severity of the corneal injury evoked by individual noxes, and the resulting changes in corneal hydration and transparency. CONCLUSIONS: The influence of various influences applied to the cornea, manifested as changes in corneal light transmission, can be measured using our spectrophotometric method with a high degree of sensitivity.
Keywords: rohovka; edém rohovky; Hydrochloric Acid; Corneal Edema; Sodium Hydroxide; světlo; hydroxid sodný; zvířata; králíci; kyselina chlorovodíková; Light; Spectrophotometry; Rabbits; spektrofotometrie; Cornea; Animals